PENGARUH INFLASI, NILAI TUKAR DOLAR, RETURN ON ASSET (ROA), DEBT TO EQUITY RATIO (DER) DAN CURRENT RATIO (CR) TERHADAP RETURN SAHAM - Purnamasari, Laely (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2017)
Increased profit by the company can be done in various ways. One of them by investing in the capital market.But many things to consider in choosing the shares to be invested. The main purpose of activity in the capital market is to earn a profit (return). Investors use various means to obtain expected returns, either through their own analysis of stock trading behavior, or by taking advantage of advice provided by stock market analysts such as brokers, dealers, investment managers and others. Statistical methods used in this study are inferential statistics, while the type of research used is descriptive verification research. The sample in this study are property and real estate listed on Indonesia Stock Exchange during 2009-2012. Analyzer used in this research use multiple regression. In this research, there is influence Inflation, Dollar Exchange Rate, Return On Asset (ROA), Debt to Equity Ratio (DER) and Current Ratio (CR) to stock return simultaneously and significantly. The value of influence Inflation, Dollar Exchange Rate, Return On Assets (ROA), Debt to Equity Ratio (DER) and Current Ratio (CR) to stock return of 26.8%.